INNOVATIVE WORK BEHAVIOR AND INFLUENCING FACTORS - Satria Efandi Efandi; Muhammad Nur Syuhada (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Innovation serves as capital in the face of business competition, and innovation must be realized in the form of real action, namely in the form of innovative work behavior. Innovative work behavior plays a major role in increasing productivity and profit for a company or organization because of its originality. This article discusses innovative work behavior, dimensions and stages of innovative work behavior, and factors that influence innovative work behavior. The method used is literature review from 33 journals on innovative work behavior. The findings are that innovative work behavior is the behavior of creating new things for the benefit of the organization which consists of exploration, generation, fighting for and implementing ideas that are influenced by internal factors of employees and external factors in the form of environment and work situations.